Vowel Shifting as a Marker of Social Identity in the Portuguese Dialect of Nordeste, São Miguel (Azores). - Silva, David J. (Luso-Brazilian Review, 2005)
Examines the pronunciation of stressed vowels in São Miguel Portuguese by extending a Labovian quantitative analysis to the observed variation between non-shifted and shifted forms in the entire vowel space. Comparison of the stressed vowels of São Miguel Portuguese and standard European Portuguese; Frequency of shifted stressed vowels by style.